Representing the Past in Visual Narratives Case Study: The Last Step (Pelleye Akhar) and Le Passé (Gozashte) - Mostafa DashtiAhangar; Arezoo Ashkani (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Similar to other written and visual narratives, Cinema reflects social and cultural values, and therefore, it has much to offer to interdisciplinary approaches to language and culture. It is possible to examine connections between the text and the society via discourse analysis and attending to the details of such texts, which could offer valuable findings to researchers. Among relevant methods in discourse analysis, Laclau and Mouffe’s approach (known as Discourse theory) is an efficient method in analyzing texts in which social references are of importance, since on the one hand, Discourse theory is rooted in Marxism, and on the other hand, it views the phenomena from the perspective of the poststructuralism. The purpose of this paper is to offer a model to study discourses on the Past in narrative texts. Today, it seems that the Past has become a problematic motif in narrative texts, and therefore, it is important to study the theme of the Past in contemporary texts. Thus, this paper draws on Discourse theory and semiotics to analyze pastism in two Iranian movies: The Last Step (Pelleye Akhar) (2012) and Le Passé (Gozashte) (2013). The results indicate that the past is represented as different discourses including, elimination, reprisal, return and fixation. Each of these discourses can represent a particular manner to encounter the past on the part of different social classes.